Development of Interactive Teaching Materials in Editlinguistic Lectures Assisted by The Lectora Application - Suhud Aryana; Rifa Salsabila (IKIP PGRI Bojonegoro, 2024)
This research endeavors to enhance interactive teaching materials for editing courses, aiming to boost student interaction and comprehension of editing content with Lectora application support. The methodology encompasses the design, development, and evaluation of these materials, along with assessing the success of Lectora application-based instruction. The study involves IKIP Siliwangi Semester 5 class A1-2021 students as the population and research sample. Findings reveal a high material expert validation level (90%) and media validation (96.5%), indicating excellent criteria. Statistical tests demonstrate a significant difference (Asymp. Sig. < 0.05) in linguistic editing skills understanding and mastery between students exposed to interactive teaching materials with Lectora application assistance and those using conventional teaching materials at IKIP Siliwangi. The research aspires to positively contribute to tertiary education development, particularly in enhancing Editlinguistic learning effectiveness through a technology-based interactive approach.